Rancang Bangun Prototipe Sistem Kontrol Automatic Main Failure (AMF) Menggunakan SMS (Short Message Service) Berbasis PLC (Programmable Logic Controller) - Defi, Sry; Pagiling, Luther; Nur, Muhammad Nadzirin Ansari; Larobu, Feliks Eldad; Jalil, Abdul; Badia, Bahdin Ahad (Jurnal Mekanova : Mekanikal, Inovasi dan Teknologi, 2024)
AMF is an Automatic Main Failure is an electrical circuit on the panel that works to turn off or turn on the generator set (generator). The standard principle is that if the PLN power is off then the AMF panel instantly turns on the generator and discharges the power supply. However, there are still many things that need to be developed in the AMF system, such as remote control and AMF monitoring. In this research, applied remote control system and monitoring of condition of generator and PLN which implemented in a prototipe panel which subsequently analyzed the working ability of each sub system. This AMF-based PLC system is combined with arduino nano microcontroller and gsm sield. PLC is used as an AMF system, arduino is used as input and output communication between PLC and GSM. Remote control system is done by SMS that utilizes GSM sield communication, to heat the generator machine and for monitoring, GSM sield will send SMS in the condition of PLN and genset of destination number which have been included in arduino nano program. The results of this study indicate that the system works well.